Single incision and reduced port laparoscopic low anterior resection for rectal cancer: initial experience in 96 cases. Issue 5 (18th July 2014) - Jung, Kyung Uk; Yun, Seong Hyeon; Cho, Yong Beom; Kim, Hee Cheol; Lee, Woo Yong; Chun, Ho‐Kyung
Abstract: Background: Although a single incision laparoscopic (SIL) technique has been used increasingly in colorectal surgery, there are only a few reports on the clinical availability of this approach coupled with low anterior resection (SIL–LAR) for colorectal cancers. We report here 96 consecutive cases of SIL–LAR and reduced port LAR cases, of which the initial approach was SIL. Methods: This is a retrospective review of prospectively collected data of SIL–LAR cases performed by a single surgeon in Samsung Medical Center between June 2011 and June 2012. Results: Out of 96 cases, 28 were finished as 'pure' SIL–LAR. Sixty‐four cases were performed with one additional port, and four needed two more ports. There was no open conversion. The median duration of operation was 165 min. Proximal and distal resection margins were negative in all cases. Circumferential resection margins were positive in four cases. The median duration of postoperative stay was 7 days and the complication rate was 20%. There were six cases of anastomosis leakage (6%). Conclusion: The SIL–LAR technique can be applied safely with the optional use of an additional port. One additional port in the right suprapubic area is useful for obtaining a secure distal division and a safe total mesorectal excision, especially in patients with lower lesions or history of neoadjuvant chemoradiation.